The Influence of Health Education Based on Health Belief Model Theory on Behavior to Prevent Postoperative Complications - Janah, Indra Ayu Miftakhul; Yuswanto, Tri Johan Agus; Sepdianto, Tri Cahyo; Suprajitno, Suprajitno (Poltekita: Jurnal Ilmu Kesehatan, 2024)
The danger of postoperative complications can prolong the healing process so prevention is needed by improving patient behavior. Health education based on the Health Belief Model can be applied to improve behavior based on patient perceptions. This research aims to prove the effect of health education based on the Health Belief Model theory on behavior to prevent postoperative complications with spinal anesthesia. This research used a True Experiment design with a Pretest-Posttest Control Group Design approach involving 60 respondents taken using a simple random sampling technique. The results of the analysis prove that there is an influence of health education based on the Health Belief Model theory on behavior to prevent postoperative complications with spinal anesthesia. The health education provided increases respondents' knowledge about preventing post-operative complications, and with the knowledge they have, it encourages respondents to improve their attitudes and behavior in preventing postoperative complications with spinal anesthesia.